No‐show after extracorporeal shock wave lithotripsy treatment in endourology clinic: Can we build a typical patient profile?. (18th March 2022) - Mekayten, Matan; Mekayten, Hadass; Rimbrot, Daniel; Shmueli, Liora; Duvdevani, Mordechai
Abstract : Objectives: Patients "no‐show" in outpatient clinics is a worldwide challenge. Healthcare providers and patients suffer from negative impacts that include increased expenditure, clinical management ineffectiveness, and decreased access to care. This study aims to evaluate no‐show rate among extracorporeal shock wave lithotripsy patients visiting endourology clinic and to identify the demographic and clinical predictors of no‐show. Methods: A cross‐sectional and historical cohort study using electronic medical records. We included 790 patients aged >18 years old referred for endourology clinic following shock wave lithotripsy during 2010–2017 at Hadassah Medical Center in Israel. We predicted no‐show rate following shock wave lithotripsy by various patient characteristics by a multivariate logistic regression model. Results: Overall, 291 (36.8%) patients did not arrive for postoperative clinic. Of these, 91 (11.52%) patients referred to Emergency Department. Patients who were younger in age (odds ratio 1.49, 95% confidence interval 1.08–2.04), patients who underwent hospitalization ≥3 days (odds ratio 1.63, 95% confidence interval 1.11–2.41) and patients who had undergone a stent‐free shock wave lithotripsy (odds ratio 5.71, 95% confidence interval 2.40–13.57) were significantly associated with higher no‐show rate. Larger stone size was associated with reduction in no‐show rate with every millimeter increase of stone diameter was associated with a reduction of 6.1% probability for no‐show (odds ratio 0.94, 95% confidence interval 0.89–0.99). Conclusions: Predicting patients' characteristics and no‐show patterns is necessary to improve clinical management efficiency, access to care, and costs. We showed that patients who were younger, patients who underwent stent‐free shock wave lithotripsy, patients who had a smaller stone, and patients who underwent a longer hospitalization were more prone to miss their appointment. Paying attention to the characteristics of individual patients may assist in implementing intervening program of patient scheduling.